LiCl induces TNF-α and FasL production, thereby stimulating apoptosis in cancer cells - Thiele Wilko; Nazarenko Irina; Marinescu Gabriela; Kaufmann Larissa; Oberle Carolin; Sleeman Jonathan; Blattner Christine (Cell Communication and Signaling, 2011)
Abstract Background The incidence of cancer in patients with neurological diseases, who have been treated with LiCl, is below average. LiCl is a well-established inhibitor of Glycogen synthase kinase-3, a kinase that controls several cellular processes, among which is the degradation of the tumour suppressor protein p53. We therefore wondered whether LiCl induces p53-dependent cell death in cancer cell lines and experimental tumours. Results Here we show that LiCl induces apoptosis of tumour cells both in vitro and in vivo. Cell death was accompanied by cleavage of PARP and Caspases-3, -8 and -10. LiCl-induced cell death was not dependent on p53, but was augmented by its presence. Treatment of tumour cells with LiCl strongly increased TNF-α and FasL expression. Inhibition of TNF-α induction using siRNA or inhibition of FasL binding to its receptor by the Nok-1 antibody potently reduced LiCl-dependent cleavage of Caspase-3 and increased cell survival. Treatment of xenografted rats with LiCl strongly reduced tumour growth. Conclusions Induction of cell death by LiCl supports the notion that GSK-3 may represent a promising target for cancer therapy. LiCl-induced cell death is largely independent of p53 and mediated by the release of TNF-α and FasL. Key words: LiCl, TNF-α, FasL, apoptosis, GSK-3, FasL